Pengaruh Gaya Hidup Berbelanja, Fear Of Missing Out, Dan Potongan Harga Terhadap Pembelian Impulsif Produk Miniso Di Shopee (Studi Kasus Pada Mahasiswa Prodi Manajemen Angkatan 2020 Universitas Bhayangkara Jakarta Raya) - Tesalonika Roliyanah; Wirawan Widjanarko; Franciscus Dwikotjo Sri Sumantyo; Matdio Siahaan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research using a quantitative research method where the sampling technique used is simple random sampling with the calculation of the sample size using the Slovin formula. The sample size used in this research was 120 respondents and focused on Miniso consumers who were students at Bhayangkara University Jakarta Raya. The results of this study show that there are variables that have an effect and that have no effect, as brief explanation: 1) The shopping lifestyle partially has a positive and significant effect on impulse buying. 2) Fear of missing out partially has no effect and is not significant on impulse buying. 3) Partial price cuts have no effect and are not significant on impulse purchases. 4) Shopping lifestyle, fear of missing out and price cuts simultaneously have a positive and significant effect on impulse buying